2015
DOI: 10.1186/s12918-015-0169-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased robustness of early embryogenesis through collective decision-making by key transcription factors

Abstract: BackgroundUnderstanding the mechanisms by which hundreds of diverse cell types develop from a single mammalian zygote has been a central challenge of developmental biology. Conrad H. Waddington, in his metaphoric “epigenetic landscape” visualized the early embryogenesis as a hierarchy of lineage bifurcations. In each bifurcation, a single progenitor cell type produces two different cell lineages. The tristable dynamical systems are used to model the lineage bifurcations. It is also shown that a genetic circuit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 53 publications
3
23
0
Order By: Relevance
“…This type of regulatory switches (Figure 1.a) are so sensitive to mutations and perturbations that directly affect the cell fate in the population. It suggests designing more complex regulatory networks consisting of a pair of clusters, with multiple elements in each, to determine the final cell fate [36]. It is revealed that these hypothesized clusters existed in biological regulatory circuitries through a literature review [65][66][67][68][69][70][71][72][73][74][75][76][77][78].…”
Section: B More Complex Switchesmentioning
confidence: 99%
See 4 more Smart Citations
“…This type of regulatory switches (Figure 1.a) are so sensitive to mutations and perturbations that directly affect the cell fate in the population. It suggests designing more complex regulatory networks consisting of a pair of clusters, with multiple elements in each, to determine the final cell fate [36]. It is revealed that these hypothesized clusters existed in biological regulatory circuitries through a literature review [65][66][67][68][69][70][71][72][73][74][75][76][77][78].…”
Section: B More Complex Switchesmentioning
confidence: 99%
“…The extended switch results in more robustness against perturbations. The buffering effect is achieved by presence of more elements and the positive feed-backs in each cluster [36]. It is expected that this effect would be even stronger in more complex switches, which is in agreement with the Waddington's idea of "canalisation" in [79]: "canalisations are more likely to appear when there are many cross links between the various processes, that is to say when the rate of change of any one variable is affected by the concentrations of many of the other variables".…”
Section: B More Complex Switchesmentioning
confidence: 99%
See 3 more Smart Citations